2019
DOI: 10.3390/ma12193094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Silicate Slag on Hydration of Cementitious Pastes

Abstract: Calcium silicate slag (CSS) is waste slag and it contains a large amount of beta-dicalcium silicate. This study is mainly focused on the effect of CSS on the hydration of cementitious pastes. CSS was used to partly replace cement, and composite pastes containing CSS and cement were prepared. The mineral composition and particle size distribution of CSS were characterized. The chemically combined water of the paste sample was measured at a given test age. Based on the value of chemically combined water, the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Bai et al [ 17 ] showed that CSS promoted the degree of hydration of cement, and that the hydration of β-C 2 S to produce Ca(OH) 2 decreased with the increasing substitution of CSS. Shi et al [ 18 ] demonstrated the use of calcium silicate slag and blast furnace slag to prepare cementitious materials, and that the compressive strength could reach more than 65 MPa when CSS was dosed at 30% and cured for 28 d. Zhang et al [ 19 ] studied the hydration of cementitious materials based on CSS. Their results showed that as the CSS replacement rate increased, the chemically bound water decreased and the spherical gel observed in the microstructure decreased, which improved the degree of hydration and reduced the heat of hydration.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al [ 17 ] showed that CSS promoted the degree of hydration of cement, and that the hydration of β-C 2 S to produce Ca(OH) 2 decreased with the increasing substitution of CSS. Shi et al [ 18 ] demonstrated the use of calcium silicate slag and blast furnace slag to prepare cementitious materials, and that the compressive strength could reach more than 65 MPa when CSS was dosed at 30% and cured for 28 d. Zhang et al [ 19 ] studied the hydration of cementitious materials based on CSS. Their results showed that as the CSS replacement rate increased, the chemically bound water decreased and the spherical gel observed in the microstructure decreased, which improved the degree of hydration and reduced the heat of hydration.…”
Section: Introductionmentioning
confidence: 99%